2007
DOI: 10.1097/bor.0b013e32802bf79d
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in rheumatoid arthritis: incorporating the patient perspective

Abstract: Recent studies have shown both that rheumatologist and patient approaches to achieving wellness differ and providing patients with a sense of control in reaching that state of wellness leads to better outcomes. Current research is focused on evaluating how best to measure the patient assessments and incorporate the patient voice into the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Fatigue is increasingly recognized as an important factor contributing to quality of life in RA patients, and persistent fatigue is one of the biggest obstacles to optimizing function in these patients (Heller and Shadick, 2007). Progression of RA disease varies considerably from person to person, and is affected by a range of immune, neuroendocrine, and psychosocial factors (Uhlig et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is increasingly recognized as an important factor contributing to quality of life in RA patients, and persistent fatigue is one of the biggest obstacles to optimizing function in these patients (Heller and Shadick, 2007). Progression of RA disease varies considerably from person to person, and is affected by a range of immune, neuroendocrine, and psychosocial factors (Uhlig et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Where the pannus tissue encroaches on periarticular bone, erosions occur through coupling of inflammation to osteoclast formation. Damage to articular cartilage and periarticular bone results in irreversible joint dysfunction and reduces quality of life (17). Knowledge of these basic mechanisms of RA pathogenesis has led to clinical approval of targeted biologic therapeutics that (a) block proinflammatory cytokines, (b) interrupt T cell costimulation, and (c) deplete B cells (18,19).…”
Section: Inflammatory Arthritis -Dysregulation Of Bone Remodeling Ranmentioning
confidence: 99%
“…However, some indicated that they had missed information on how medication could affect their daily lives or how to minimize the impact of the administration schedule on their daily lives. The need to stay in control and the need for practical information is in line with studies showing that patients prioritize treatment outcomes related to quality of life (129)(130)(131)(132)(133)(134)138). To increase patients' involvement in medical decisionmaking, it is essential to not only inform patients about clinical elements of the treatment, but also about the impact on lifestyle, control and comfort.…”
Section: ] If You Have Little Information There's Little To Worry Amentioning
confidence: 96%
“…If patients completely rely on the expertise of their rheumatologist, they may fail to recognise the potential value of their own input (38). Since rheumatologists' and patients' beliefs about treatment differ (120,(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139), the input of patients seems important. Moreover, patients' adherence to treatment might increase if it matches their preferences.…”
Section: ] If You Have Little Information There's Little To Worry Amentioning
confidence: 99%
See 1 more Smart Citation